2019
DOI: 10.5089/9781498314565.001
|View full text |Cite
|
Sign up to set email alerts
|

Case Studies in Tax Revenue Mobilization in Low-Income Countries

Abstract: How can Low-Income Countries (LICs) enhance tax revenue collection to finance their vast development needs? We address this question by analyzing seven tax reform experiences in LICs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 8 publications
0
19
0
5
Order By: Relevance
“…Far more frequently, however, demand for government revenue expansion was used to justify the design and implementation of measures. 24,46,48,51,53,60,78,91,92,100,109,126 This was commonly linked to shrinking revenue from exports, 91 increased demand for public expenditure, 48,91 the ramifications of trade liberalisation on import tariffs 24,51,53,78,100 and state-ownership or monopolies. 46,92,109 While revenue generation motives were effective in garnering initial support from economicallyinterested parties, as articulated by Kaiser et al, 48 the design of measures necessitates the incorporation of a broader perspective, such as good governance or pro-poor sentiments, to sustain necessary backing from stakeholders.…”
Section: Situational Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Far more frequently, however, demand for government revenue expansion was used to justify the design and implementation of measures. 24,46,48,51,53,60,78,91,92,100,109,126 This was commonly linked to shrinking revenue from exports, 91 increased demand for public expenditure, 48,91 the ramifications of trade liberalisation on import tariffs 24,51,53,78,100 and state-ownership or monopolies. 46,92,109 While revenue generation motives were effective in garnering initial support from economicallyinterested parties, as articulated by Kaiser et al, 48 the design of measures necessitates the incorporation of a broader perspective, such as good governance or pro-poor sentiments, to sustain necessary backing from stakeholders.…”
Section: Situational Factorsmentioning
confidence: 99%
“…However, some promise is found in recent support for fiscal measures by the IMF and World Bank and the implementation of measures by conservative governments. 24,60,126 The altered stance of these agencies and governments demonstrates the possibility of reorientating the neoliberal agenda to recognise the importance and potential returns associated with investing in the health of 'human capital. ' 136 Further research is necessary to explore the breadth of neoliberalism's influence, as we currently have an incomplete picture of the barriers, tensions and political opportunities in assessing the feasibility of fiscal measures as a form of responsive public policy.…”
Section: Contextmentioning
confidence: 99%
“…Our research revealed that a high-level political commitment and buy-in from all stakeholders played a crucial role for success. These findings are further discussed in the follow-up papers on cases studies (Akitoby et al 2018a, Akitoby et al 2018b, and Akitoby et al 2018c The paper is organized as follows: Section II discusses recent tax revenue developments in LICs and EMs, and Section III provides a description of the revenue data. Section IV outlines the analytical framework for identifying revenue mobilization episodes and discusses the findings from these episodes.…”
Section: Introductionmentioning
confidence: 99%
“…The two hypotheses would have different policy implications, calling for careful scrutiny. If Hypothesis 1 (tax capacity→institutions) holds, countries (especially with poor institutions and low tax capacity) should first work on reform measures that will produce immediate short-term rise in tax capacity (Akitoby et al, 2019). 5 Such revenue enhancing efforts would help improve institutions.…”
mentioning
confidence: 99%
“…For instance, starting with efficient tax policies and revenue administration changes (i.e. tax rate, tax exemptions and risk management), tax revenue could be boosted over the short-term (Akitoby et al 2019). However, the proceeds from these short-term changes could be used to implement expensive institutional reforms that will lead to general improvement in state institutions.…”
mentioning
confidence: 99%